ARTIFICIAL INTELLIGENCE IN DEVELOPING COUNTRIES: CHALLENGES AND OPPORTUNITIES — AN AFRICAN VIEW AND ITS APPLICATION IN ANGOLA - de Lima Pacheco, Marcio; Chagas Ramos, Rawy; Samoma Fernando, João (Revista Gênero e Interdisciplinaridade, 2025)
This paper presents the impact of artificial intelligence (AI) in developing countries, particularly in the African context, identifying the challenges and opportunities that this technology offers. AI emerges as a potential tool to transform various sectors, including health, education, and agriculture, in countries like Angola. Although the current context presents many opportunities, it also faces significant challenges, such as insufficient infrastructure, the need for capacity building, and lack of regulation. The research aims to understand the impact of AI in critical sectors and evaluate the conditions for its effective adoption. The methodology used involves a systematic bibliographic review of programs, articles, books and reports, with a focus on recent publications. This study uses a qualitative research based on interpretative analysis of data obtained from various sources, including websites, libraries, and national organizations, allowing for the articulation of existing studies on the topic and understanding the reality of AI in developing countries. Overall, the negative impacts may include dependence on technological companies and infrastructure from developed countries, inequality in access to technologies, and ethical and regulatory challenges. Among the study’s limitations are the lack of specific data on AI implementation in Angola and inequality in access to technology between urban and rural areas.